Inova????o: a compreens??o dos envolvidos com o ensino superior em Bras??lia - Souza, Caroline Nagel Moura de (2012)
This research aims to understand the general meaning of innovation in higher education, from the actors involved in the process: University of Bras??lia, Ministry of Education and Culture and the Ministry of Science, Technology and Innovation. We tried to identify, in the universities of the city of Bras??lia, elements of social policies for creating innovations, through its official documents and in the case of ministries to analyze the policies, projects and normative acts effectively as they intended and invest resources in the development and implementation of the theme. We sought to further understand the potential and limits of the University in the development of the country, questioning the prevailing educational paradigm, especially in higher education, making a link between education, the concept of quality and labor market prospects. The issue arises, try to understand how effectively these actors involved in higher education has dealt with the issue, and how proposed innovations are transforming, structural, which will allow the common good, which can be defined as innovations that carry with them the many benefits people thus forming individuals capable of changing a setting devoid of development. She longs to meet a need of the present scenario of higher education, which is to prepare yourself for the constant changes and continuing uncertainty about the future path of development and progress and economic, social and political development of the country. So therefore it will reveal that lack understanding about innovation from the perspective of quality education.